2021
DOI: 10.1515/nanoph-2020-0593
|View full text |Cite
|
Sign up to set email alerts
|

Quantum nanophotonic and nanoplasmonic sensing: towards quantum optical bioscience laboratories on chip

Abstract: Quantum-enhanced sensing and metrology pave the way for promising routes to fulfil the present day fundamental and technological demands for integrated chips which surpass the classical functional and measurement limits. The most precise measurements of optical properties such as phase or intensity require quantum optical measurement schemes. These non-classical measurements exploit phenomena such as entanglement and squeezing of optical probe states. They are also subject to lower detection limits as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 373 publications
(507 reference statements)
1
39
0
Order By: Relevance
“…Summarizing, we have demonstrated that thermo-hydrodynamic boundary flows can manipulate nano-objects with unprecedented flexibility in a very simple sample geometry. These flows are the key for future thermo-optofluidic implementations with an extensive range of applications in the fields of (i) nanoparticle sorting and separation; (ii) assembly of nanophotonic circuits 47 and plasmonic quantum sensors 4 , 5 ; (iii) biotechnology on-chip laboratories 48 and (iv) manufacturing of nanomaterials 4 , 6 and functional nanosurfaces 49 , 50 . We have substantiated our experimental findings of thermo-osmotic flow-assisted trapping with a quantitative theoretical description.…”
Section: Resultsmentioning
confidence: 99%
“…Summarizing, we have demonstrated that thermo-hydrodynamic boundary flows can manipulate nano-objects with unprecedented flexibility in a very simple sample geometry. These flows are the key for future thermo-optofluidic implementations with an extensive range of applications in the fields of (i) nanoparticle sorting and separation; (ii) assembly of nanophotonic circuits 47 and plasmonic quantum sensors 4 , 5 ; (iii) biotechnology on-chip laboratories 48 and (iv) manufacturing of nanomaterials 4 , 6 and functional nanosurfaces 49 , 50 . We have substantiated our experimental findings of thermo-osmotic flow-assisted trapping with a quantitative theoretical description.…”
Section: Resultsmentioning
confidence: 99%
“…The use of quantum light states in integrated optical devices allows to develop different on-chip applications in quantum optical communications and in other fields such as quantum photonic simulations [196] and quantum photonic sensing [218]. Rigorous theories of linear and nonlinear quantum spatial propagation states in integrated waveguides can be used [219][220][221][222], which allows us to study and design linear and nonlinear quantum integrated optical elements.…”
Section: Fundamental Aspects Of Quantum Integrated Optical Componentsmentioning
confidence: 99%
“…Generally we expect a large Fisher information when probabilities change most quickly with respect to the parameter of interest, while it vanishes at the extrema of the probabilities as there is no local information at these points; Eq. (26) shows that the Fisher information must vanish whenever the derivative of all probabilities is zero.…”
Section: Appendix D: Noise Resilience Of Independent Photonsmentioning
confidence: 99%